From «Metahistory» to «The Practical Past»: Rhetoric, Narrative and Ideology in Hayden White - Pérez Baquero, Rafael (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
The purpose of the article is to develop a diachronic interpretation of Hayden White´s thought in order to reveal its most relevant assumptions and the different discontinuities of his works. In this sense, the changes of his theory should be understood taking into account the variations of the relationships between the rhetoric dimension and ethic-political dimension. The first one is structural at his earlier works and the second is structural at the latter. Besides, this variation is a consequence of the modifications of his theory of language. These modifications consist in the emphasis of the performative condition of the poetic function of historical discourse.
Keywords: tropology; narrative; ideology; performative; metahistory; irony